KUALITAS PELAYANAN SERTIFIKAT TANAH DI KANTOR PERTANAHAN KOTA ADMINISTRASI JAKARTA SELATAN - Eka Prasojo; Mawar Mawar (Universitas Muhammadiyah Jakarta, 2017)
The institution that have authority to handle national land affair is Badan Pertanahan Nasional (national land affair institution) it has function to manage land affair administration, especially in land affair administration office of south jakarta to increase services to society. And then the problem formulation is how about the quality n services of land certificate in land affair office of South Jakarta administration. And about both of the proponent factor and obstruction factor in implementation. This research use Zeithaml theory, Berry n Parasuraman 1985 with descriptif and qualitatif methode, where reseacher descript the phenomena by analizing and serving fact sistematically to make easier in understanding and resume the conclusion. Data sources come from interview, documentation and observation. Data analizing by interactive model analizing with 3 step action that are reduction data, data serving and resume conclusion. Based on research result can be concluded that the quality of certificate services was still not good. It was analized by direct indicator. The location of land affair office was regarded not switable. Parking area facility was narrow and suggestion box have not use yet well. Indicator of target reliable, target of finishing land certificate spend long time and not according standart established. The indicator of perspective socialization program by land affair institution not be done optimally rontie and, overall. Guaranted indicator, the competency of employed not as criteria and not in equal need improvement, emphaty indicator, there are employe do not in friendly. The need of society to make certificate can not be carried but not yet completely. Endorsement factor were regulation, organization, income ability, and skill, and also series equipment, while abstruction factor are, laek of cooperation between society to fulfill reqruitment and society awareness to make land certificate.Keywords: Public Services, quality, Land certificate